2020
DOI: 10.1021/jacs.9b07820
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Co-translational Membrane Protein Integration and Translocation via the Sec Translocon

Abstract: An important aspect of cellular function is the correct targeting and delivery of newly synthesized proteins. Central to this task is the machinery of the Sec translocon, a transmembrane channel that is involved in both the translocation of nascent proteins across cell membranes and the integration of proteins into the membrane. Considerable experimental and computational effort has focused on the Sec translocon and its role in nascent protein biosynthesis, including the correct folding and expression of integ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 86 publications
0
13
0
1
Order By: Relevance
“…Nevertheless, it should also be noted that the translation of this segment occurs as TM2 begins to emerge from the exit tunnel and interact with the translocon and/ or membrane. Modifications that alter the translation kinetics within this region could therefore also impact the membrane integration of TM2 and pulling forces on the nascent chain (Niesen et al, 2020). To evaluate the potential role of translational kinetics, we calculated mKate: eGFP intensity ratios associated with each individual codon substitution, then sorted the values for each codon according to the relative abundance of their decoding tRNAs in HEK293 cells (see Methods ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, it should also be noted that the translation of this segment occurs as TM2 begins to emerge from the exit tunnel and interact with the translocon and/ or membrane. Modifications that alter the translation kinetics within this region could therefore also impact the membrane integration of TM2 and pulling forces on the nascent chain (Niesen et al, 2020). To evaluate the potential role of translational kinetics, we calculated mKate: eGFP intensity ratios associated with each individual codon substitution, then sorted the values for each codon according to the relative abundance of their decoding tRNAs in HEK293 cells (see Methods ).…”
Section: Resultsmentioning
confidence: 99%
“…Mutations that increase the relative abundance of decoding tRNAs and accelerate translation could potentially decrease - 1PRF by reducing the efficiency of translocon-mediated membrane integration (Niesen et al, 2020). To assess how translational kinetics impact the membrane integration of TM2, we carried out a series of CGMD simulations of polyprotein biosynthesis in which the rate of translation was varied.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the structural changes of the translocon are essential for translocon-assisted protein insertion, many MD simulation studies focused on the conformational changes of the prokaryotic and eukaryotic Sec channels [ 15 , 36 , 37 , 38 , 39 , 40 ]. Furthermore, MD simulation studies explored how the Sec61 channel recognizes substrate peptides and directs them either to membrane insertion or translocation [ 41 , 42 , 43 , 44 , 45 , 46 ]. The contribution of thermodynamics and kinetics and the detailed role of the translocon in the exit mechanism were also explored by 2D and 3D coarse-grained simulations [ 47 , 48 ].…”
Section: Conformational Dynamics Of the Sec61 Translocon And Bound Sps In Molecular Dynamics Simulationsmentioning
confidence: 99%
“…Their simulation results also demonstrated that increasing the length of the C-terminal loop of the TM segment raises the probability that the TM segment adopts a type II topology (N /C ). Their studies helped to elucidate the effects of sequence, translation rate, and external forces on the probability of nascent-chain integration into the membrane and to rationalise the resulting orientation of TMDs with respect to the membrane [ 44 ]. Besides, by combining site-directed mutagenesis in the yeast Sec61 translocon (in vivo) and MD simulations of SecY, it was shown that the membrane insertion propensity of signal-anchor sequences strongly depends on the positions of hydrophobic residues in the sequence segment and on its interaction with the six pore ring residues [ 41 ].…”
Section: Conformational Dynamics Of the Sec61 Translocon And Bound Sps In Molecular Dynamics Simulationsmentioning
confidence: 99%